Comparative proteomic analysis of fluoride treated rat bone provides new insights into the molecular mechanisms of fluoride toxicity. (July 2018) - Wei, Yan; Zeng, Beibei; Zhang, Hua; Chen, Cheng; Wu, Yanli; Wang, Nanlan; Wu, Yanqiu; Zhao, Danqing; Zhao, Yuxi; Iqbal, Javed; Shen, Liming
Highlights: NaF has profound dose-dependent effect on bones in SD rats. A total of 63 differentially expressed proteins are identified between the NaF- treated groups and control group. Some key proteins and signal transduction pathways are involved affecting the bone tissue. Twelve (12) proteins are being first time reported to be associated with the fluoride study on bone tissue. Abstract: Long-term excessive intake of fluoride (F) could lead to chronic fluorosis. To explore the underlying molecular mechanisms, present study is designed to elucidate the effect of fluoride on proteome expression of bone in sodium fluoride (NaF)-treated SD rats. Hematoxylin and eosin (H&E) staining was used to determine the severity of osteofluorosis, and bone samples were submitted for iTRAQ analysis. The results showed that the cortical thickness and trabecular area of femur bone in medium- and high-dose groups were higher than in control group. Contrary to this, trabecular area was reduced in the low-dose group, indicating that the bone mass was increased in medium- and high-dose groups, and decreased in the low-dose group. Thirteen (13), 35, and 34 differentially expressed proteins were identified in low-, medium-, and high-dose group, respectively. The medium- and high-dose groups shared a more similar protein expression pattern. These proteins were mainly associated with collagen metabolism, proteoglycans (PGs), matrix metalloproteinases (MMPs), etc. The results suggested that the effect of NaF on SD rats is in a dose-dependent manner. Some key proteins found here may be involved in affecting the bone tissues and bone marrow or muscle, and account for the complex pathology and clinical symptoms of fluorosis.